Synthesis of Cinnolines via Rh(III)‐Catalyzed Annulation of N‐Aryl Heterocycles with Vinylene Carbonate. Issue 11 (22nd October 2021) - Kim, Suho; Choi, Su Bin; Kang, Ju Young; An, Won; Lee, Suk Hun; Oh, Harin; Ghosh, Prithwish; Mishra, Neeraj Kumar; Kim, In Su
Abstract: The Rh(III)‐catalyzed C−H annulation reactions of N ‐aryl indazolones or N ‐aryl phthalazinones with a vinylene carbonate is described herein. This transformation provides the rapid access to indazolocinnolines and phthalazinocinnolines as important assets towards the development of novel bioactive compounds. Intriguingly, a vinylene carbonate acts as a vinyl transfer agent to enable the [4+2] annulation reaction. This method is characterized by its simplicity, mild reaction conditions, and broad functional group tolerance. Abstract : The Rh(III)‐catalyzed C−H annulation reactions of N ‐aryl indazolones or N ‐aryl phthalazinones with a vinylene carbonate for the construction of indazolocinnolines and phthalazinocinnolines is described herein.